YouTube and 'psychiatry'. (December 2015) - Gordon, Robert; Miller, John; Collins, Noel
Summary: YouTube is a video-sharing website that is increasingly used to share and disseminate health-related information, particularly among younger people. There are reports that social media sites, such as YouTube, are being used to communicate an anti-psychiatry message but this has never been confirmed in any published analysis of YouTube clip content. This descriptive study revealed that the representation of 'psychiatry' during summer 2012 was predominantly negative. A subsequent smaller re-analysis suggests that the negative portrayal of 'psychiatry' on YouTube is a stable phenomenon. The significance of this and how it could be addressed are discussed.